Kedudukan Hukum Islam dalam Penanganan Perkara Waris di Indonesia - Ajis Supangat (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the position of Islamic inheritance law within Indonesia’s pluralistic national legal system, where Islamic inheritance law exists alongside customary inheritance law and Western civil inheritance law. The focus of the study is on the implementation of the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) as positive law in the settlement of inheritance cases for Muslims within the jurisdiction of the Religious Courts. Using a literature and documentation-based research approach, this study presents findings that, although KHI has become a normative guideline, its implementation in the field still faces various challenges, such as the public’s limited understanding of Islamic inheritance law, the strong influence of customary law, and the lack of administrative documents. Furthermore, the ununified legal pluralism results in different inheritance practices across regions. The findings indicate that judges in the Religious Courts tend to apply the provisions of the KHI consistently particularly Articles 171–214 while still taking into account local cultural contexts to maintain family harmony. This article recommends the importance of Islamic inheritance law education, strengthening the harmonization among legal systems, and encouraging the unification of national inheritance law to achieve legal certainty and justice comprehensively.